Right to architectural heritage preservation of urban: a challenge for local authorities - Taller, Adriana (Universidad Nacional del Litoral, 2014)
The protection of property with historical, cultural, artistic and / or architectural value, has a duty claimed to national and local administrations since it emerged in the community historical awareness, commitment to the experience. The doctrine and comparative constitutional jurisprudence recognize the cultural heritage as a fundamental human right, hence the need to incorporate into the supreme law along with other fundamental rights, the right to cultural heritage. The Argentine Constitution of 1994 enshrines the fundamental right subjective public or collective right to the preservation of cultural, urban and architectural heritage, in its substantive face (Article 41) and procedural (Article 43) incidence; to recognize its existence administrative and judicial legitimacy to exercise and defense is recognized. This close relationship between cultural heritage and the right indicates the need for indentificar and interpret these goods whose enjoyment is a collective right and that authorities and individuals have a duty to protect.